Polystyrene-Supported Polyoxyethylene Bound Permanganate as Oxidising Agent: Effect of the Nature of Crosslinking on Oxidation Behaviour - CHACKO, ASHA; MATHEW, BEENA (Asian Journal of Chemistry, 2010)
The effect of the nature of crosslinking agent on the oxidation of polystyrene supported polyoxyethylene bound permanganate is present in this paper. For this microporous rigid divinyl benzene (DVB)-crosslinked and flexible 1,6-hexanediol diarylate (HDODA)-crosslinked polystyrene were used as supports. Polyoxyethylene is incorporated by polymer-analogous reactions. Permanganate functions were incorporated by equilibration with potassium permanganate in benzene medium. The permanganatc capacity is higher for the flexible HDODAcrosslinked system. The oxidizing abilities of these heterogeneous oxidizing agents were investigated towards primary and secondary alcohols to aldehydes and ketons. The effect of various reaction parameters on oxidation behaviour was also investigated. The oxidizing ability of flexible HDODA-crosslinked system is higher than the rigid DVB-crosslinked system. The spent polystyrene-supported polyoxyethylene bound permanganate resin could be recycled and reused without loss of activity.